2018
DOI: 10.1186/s12989-018-0270-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and inflammatory mechanisms in healthy humans exposed to air pollution in the vicinity of a steel mill

Abstract: BackgroundThere is a paucity of mechanistic information that is central to the understanding of the adverse health effects of source emission exposures. To identify source emission-related effects, blood and saliva samples from healthy volunteers who spent five days near a steel plant (Bayview site, with and without a mask that filtered many criteria pollutants) and at a well-removed College site were tested for oxidative stress, inflammation and endothelial dysfunction markers.MethodsBiomarker analyses were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 73 publications
0
14
2
1
Order By: Relevance
“…1 shows the selection process of literature. We identified 44 studies from citations screened ( Chen et al., 2018 ; Chuang et al., 2007 ; Cole et al., 2018 ; Croft et al., 2017 ; Dadvand et al., 2014 ; Delfino et al., 2010 ; Deng et al., 2020 ; Dubowsky et al., 2006 ; Emmerechts et al., 2012 ; Forbes et al., 2009 ; Green et al., 2016 ; Habre et al., 2018 ; Hajat et al., 2015 ; Hassanvand et al., 2017 ; Hildebrandt et al., 2009 ; Hoffmann et al., 2009 ; Huttunen et al., 2012 ; Kumarathasan et al., 2018 ; Lanki et al., 2015 ; Lee et al., 2018 ; Liao et al., 2005 ; Mirowsky et al., 2015 ; Pekkanen et al., 2000 ; Pope et al., 2016 ; Puett et al., 2019 ; Rich et al., 2012 ; Ruckerl et al., 2007 ; Rückerl et al., 2014 ; Rudez et al., 2009 ; Schneider et al., 2010 ; Schwartz, 2001 ; Seaton et al., 1999 ; Steinvil et al., 2008 ; Strak et al., 2013 ; Su et al., 2017 ; Sullivan et al., 2007 ; Tsai et al., 2012 ; Viehmann et al., 2015 ; Wang et al., 2018 ; Wu et al., 2012 ; Zeka et al., 2006 ; Zhang et al., 2016 , 2020 ; Zuurbier et al., 2011 ). Supplemental Table S3 provides the characteristics of included studies.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…1 shows the selection process of literature. We identified 44 studies from citations screened ( Chen et al., 2018 ; Chuang et al., 2007 ; Cole et al., 2018 ; Croft et al., 2017 ; Dadvand et al., 2014 ; Delfino et al., 2010 ; Deng et al., 2020 ; Dubowsky et al., 2006 ; Emmerechts et al., 2012 ; Forbes et al., 2009 ; Green et al., 2016 ; Habre et al., 2018 ; Hajat et al., 2015 ; Hassanvand et al., 2017 ; Hildebrandt et al., 2009 ; Hoffmann et al., 2009 ; Huttunen et al., 2012 ; Kumarathasan et al., 2018 ; Lanki et al., 2015 ; Lee et al., 2018 ; Liao et al., 2005 ; Mirowsky et al., 2015 ; Pekkanen et al., 2000 ; Pope et al., 2016 ; Puett et al., 2019 ; Rich et al., 2012 ; Ruckerl et al., 2007 ; Rückerl et al., 2014 ; Rudez et al., 2009 ; Schneider et al., 2010 ; Schwartz, 2001 ; Seaton et al., 1999 ; Steinvil et al., 2008 ; Strak et al., 2013 ; Su et al., 2017 ; Sullivan et al., 2007 ; Tsai et al., 2012 ; Viehmann et al., 2015 ; Wang et al., 2018 ; Wu et al., 2012 ; Zeka et al., 2006 ; Zhang et al., 2016 , 2020 ; Zuurbier et al., 2011 ). Supplemental Table S3 provides the characteristics of included studies.…”
Section: Resultsunclassified
“…Among healthy humans, Kumarathasan et al. reported insignificant changes of TNF-α, IL-6, and IL-8 with short-term PM 2.5 exposure ( Kumarathasan et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study on healthy people who spent 5 days near a steel plant showed that both of the systolic and diastolic blood pressures were higher in those volunteers who did not use mask in this area [17].…”
Section: Environmental Emissionsmentioning
confidence: 99%
“…Finally, an important area of investigation in environmental epidemiology has been the identification of specific components in PM 2:5 that may lead to adverse health outcomes. PM 2:5 constituents differ in toxicity (Bell et al 2014;Franklin et al 2008), and some prior studies have identified a heightened effect of steelrelated airborne metals on inflammation (Ghio and Devlin 2001;Kumarathasan et al 2018).…”
Section: Introductionmentioning
confidence: 99%